Genetic dissection of seedling root architecture under aluminium toxicity in tropical maize (Zea mays L.) - Channapur, Arun M.; Kumar, Santosh; Kumar, Bhupender; Singh, Preeti; Abhijith, Krishnan P.; A., Akash; Singh, Rakhi; Belwal, Pooja; Prakash, Vijay; Jaiswal, Sandeep; Limbalkar, Omkar Maharudra; Pal, Saheb; et al. (Frontiers in Plant Science, 2026)
Aluminum (Al) toxicity is a major production constraint to tropical maize in acidic soils, primarily impairing root growth. This study aimed to dissect the genetic basis of seedling-stage root architectural traits conferring Al tolerance in tropical maize using genome-wide association study (GWAS). A hydroponic protocol was standardized by evaluating seven inbred lines under different Al concentrations, and 300μM AlCl3 at day 11 was found optimal for phenotyping. Significant reductions in root length, surface area, volume and tips ranged 24-38%, while diameter increased by 13% under stress in 250 diverse maize inbred lines. Principal component and correlation analyses indicated strong association of root elongation and branching traits, while thickening was largely independent. Genotyping with 60,227 SNPs revealed three subpopulations with moderate linkage disequilibrium decay (65.4 kb), supporting high-resolution GWAS. Mixed Linear Model analysis detected 44 significant SNPs across eight chromosomes, explaining 9.68-18.43% of phenotypic variance. Eight QTL clusters were identified, including two major hotspots on chromosomes 8 and 3 designated as “QTL hot spot A” and “QTL hot spot B” with seven and five major QTLs respectively. Candidate gene analysis highlighted 33 functionally relevant genes linked to stress tolerance, including glutathione S-transferases, Dehydroascorbate reductases, MATE transporters, and regulators of STOP1 stability and activity. In-Silico expression analysis confirmed stress-responsive regulation of several promising genes. Collectively, this study provides genomic regions and candidate genes underpinning root-based Al tolerance, offering valuable targets for marker-assisted breeding and genomic prediction in tropical maize.